Fiqh Learning Strategies for Fostering Students’ Responsibility for Worship at MAS Darul Ihsan - Nazaruddin Nazaruddin; Ahmad Darlis (Journal of Social Work and Science Education, 2027)
This study aimed to analyze the fiqh learning strategies used to foster students’ responsibility for worship at MAS Darul Ihsan, examine their implementation, and explore students’ responses and the challenges encountered. A qualitative case-study design was employed. Data were collected through in-depth interviews with fiqh teachers, homeroom teachers, and students, classroom observation, and analysis of curriculum and learning documents. The data were reduced, categorized, interpreted, and compared across sources and techniques. The findings show that teachers used contextual explanation, translation of Arabic texts, guided reading, interactive discussion, practical worship activities, supporting religious programs, and teacher modeling. Connecting fiqh concepts with daily worship helped students understand not only legal procedures but also the meaning and responsibility associated with worship. Practical activities, including worship examinations, funeral-management practice, and hajj simulations, strengthened students’ confidence, discipline, and readiness to apply their knowledge. The main challenges concerned the linguistic difficulty of Arabic texts, variations in students’ understanding, and maintaining consistency in worship. Teachers addressed these challenges through gradual translation, repeated explanation, collective reading, contextual examples, and continuous guidance. The study concludes that participatory, contextual, practice-oriented, and value-based fiqh instruction can support the internalization of worship responsibility. However, broader and longitudinal research is needed to examine the sustainability of these practices across different madrasah contexts.